The economics of Transmilenio a mass transit system for Bogotá (2004)
By the end of the 1990s, inefficiency, excess supply and low service quality characterized the mass transit system of Bogotá. The average travel time to work was one hour and ten minutes, obsolete buses provided public transport, traffic generated 70 percent of air pollution and there were frequent traffic accidents. To address all of these issues, the municipal and national governments designed and put in place a new mass transit system named TransMilenio (TM), which came into operation in January 2001. The purpose of this paper is to analyze Bogotá's mass transit system before and after TM, study the political economy of its adoption process and conduct a cost-benefit analysis (CBA) of the first phase of the system. The new transit system is a hybrid model that combines public planning of the network structure, route tendering conditions, regulation and supervision, as well as private operation of the separated functions of revenue collection and transport service. The adoption of this new model needed to resolve delicate political economy issues that characterized private transport systems in many developing countries...